IMPLEMENTASI HAK KONSUMEN PASCA PEMBERLAKUAN UNDANG-UNDANG PERLINDUNGAN KONSUMEN: A BREACH OF SOCIAL JUSTICE? - Agus Budianto (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
The implementation of Consumer Protection Act which has shown the struggle to create equality of social justice between business people and consumers still remains a binding norm. On the other hand, ignorance or infringement of consumer rights can be interpreted as a breach of social justice, because the breach of social justice is defined not as a infringement of social norms, but interpreted as an infringement of consumer rights stipulated in the Constitution of the Republic of Indonesia in particular and the rights of the public in general, as mandated in the concept of welfare state. The concept of welfare state is not an abstract concept in consumer protection law, as mandated in Article 29 verse (1) Consumer Protection Act, that a state has roles in ensuring the fulfillment of consumer rights stipulated in the constitution or in other provisions. Thus, a state has the obligation in creating equitable welfare through laws which is equal for all parties.Keywords: Consumer Protection, Social Justice